Comparison between health systems of Indonesia and Singapore: A systematic review - Nugraha, Rizki Ahmad; Paskarini, Indriati; Tualeka, Abdul Rohim (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The performance of national health systems is influenced by various internal and external factors, including governance models, financing, and geography. While both Indonesia and Singapore operate mixed public-private healthcare systems, the outcomes and challenges they face vary significantly. Understanding these differences provides critical insight into how contextual factors shape health system effectiveness. Purpose: To compare the health systems of Indonesia and Singapore by examining their structural components, similarities, differences, and challenges, with a focus on the integration of public health services. The analysis seeks to determine how contextual elements such as governance structure and geographical characteristics influence system performance. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Health systems in southeast asian countries specifically indonesia and singapore. I: Implementation and structure of the health system in Singapore, C: Health system in Indonesia, O: Comparative insights regarding efficiency, equity, accessibility, health outcomes, and quality of care between both countries, S: Systematic Review and Randomized Controlled Trials. The article search was conducted systematically using the keywords: “Health” AND “Workforce,” AND “Record,” “Vaccine Distribution,” AND “Leadership,” AND “Service Delivery,” AND “Financing System,” AND “Information System,” AND “Indonesia” OR “Singapore”. Results: Singapore’s centralized governance and compact geography enable efficient, integrated healthcare services, leading to superior health outcomes such as higher life expectancy and better physician coverage. In contrast, Indonesia’s decentralized system and geographic dispersion cause fragmented service delivery, resulting in lower life expectancy, fewer healthcare workers, and greater reliance on out-of-pocket spending. Conclusion: Singapore’s centralized and well-coordinated health system enables efficient service integration and strong health outcomes, while Indonesia’s decentralized structure and vast geography create challenges in achieving equitable and effective healthcare delivery. Strengthening governance, health workforce distribution, and digital health integration are key for Indonesia to enhance its system performance and reduce disparities.